Catalytic cracking of biomass pyrolysis tar over char-supported catalysts. (1st July 2018) - Guo, Feiqiang; Li, Xiaolei; Liu, Yuan; Peng, Kuangye; Guo, Chenglong; Rao, Zhonghao
Highlights: Char supported metallic catalysts were prepared for in situ tar cracking. The tar conversion efficiency could reach 92.6% using Fe-RHC catalyst. Active phase of K, Cu and Fe impregnated char was found to be KCl, Cu and Fe. Fe and Cu promoted the formation of porous structure to produce more active sites. Abstract: The work aims to investigate an effective method of catalytic reforming of tar during biomass high-temperature pyrolysis using rice husk char (RHC) and metal impregnated (Fe, Cu and K) char in a dual-stage reactor. The char and char-supported catalysts exhibited high catalytic performance, in terms of the high tar conversion efficiencies of 77.1% for RHC, 82.7% for K-RHC, 92.6% for Fe-RHC and 90.6% for Cu-RHC at 800 °C. Moreover, K-RHC and Cu-RHC catalysts after three cycles still exhibited high activity for tar removal. The catalytic tar conversion by char or char-supported catalysts contributes to improving the yield of syngas, particularly the combustible gases of H2, CO and CH4, corresponding to the syngas yield increasing from 196.6 mL/g for thermal reforming to 269.6 mL/g for K-RHC, 274.9 mL/g for Cu-RHC and 342.7 mL/g for Fe-RHC at 800 °C, respectively. The results from GC–MS analysis illustrated that the addition of char and char-supported catalysts promoted the transformation of larger polycyclic aromatic hydrocarbons into lighter tar compounds, leading to an increase in the proportion of single-ring tars. XRD results indicated that the most active phases of the fresh K-RHC, Cu-RHC and Fe-RHC for tar cracking and reforming were KCl, Cu and Fe, respectively. Textural characterization showed the addition of Fe and Cu was in favor of producing highly porous carbon materials and led to the increase in specific surface area and total pore volume.